The Harmonization of the Powers of the Constitutional Courts and International Judicial Authorities for the Protection of Human Rightsand Freedoms - A. A. Bakhov (Сибирское юридическое обозрение, 2018)
The Author considers the problem of the relationship between the national constitutional courts and the courts of international organizations, focusing on the analysis of existing approaches to the characterization of their relations. Considerable attention is paid to the search for the necessary balance of interaction, which would allow both institutions of judicial protection to be preserved and, at the same time, increase the effectiveness of their activities. The study is accompanied by a study of the jurisprudence of the European Court of Human Rights and the constitutional courts of European countries. Based on the study of the experience of several European countries, it is established that the problem is systemic and relevant at the international level. The Author comes to the conclusion that the way to solving the problem of conflicts of judicial institutions lies in expanding the channels of cooperation and interaction, which will strengthen the guarantees for the protection of human rights and freedoms.